Giant enhancement of superconductivity in arrays of ultrathin gallium and zinc sub-nanowires embedded in zeolite. (August 2018) - Zhang, B.; Lyu, J.; Rajan, A.; Li, X.; Zhang, X.; Zhang, T.; Dong, Z.; Pan, Jie; Liu, Y.; Zhang, J.; Lortz, R.; Lai, Z.; et al.
Abstract: We have fabricated superconducting samples comprising gallium (Ga) or zinc (Zn) infiltrated into the one-dimensional (1D) linear channels of AlPO-5 (AFI) zeolite, which have an internal pore diameter of 7 Å and are separated by an insulating wall of ∼7–9 Å. The Angstrom-scale Ga and Zn sub-nanowires, arranged in Josephson-coupled triangular arrays with an ab -plane lattice constant of 14.4 Å, display bulk superconductivity with T c values of 7.2 K and 3.7 K, respectively, which are significantly enhanced by a factor of 7 and 4 compared with their bulk values. While the zeolite template of our composite superconductor dictates the nanostructure of Ga and Zn to be 1D in the electronic sense with a highly advantageous effect for the superconducting pairing, the arrangement in a densely packed array structure avoids the shortcomings of other typical 1D superconductors, in which the coherence is usually completely suppressed by strong phase fluctuations. Graphical abstract: Image 1 Highlights: We have fabricated first sub-nanometer scale gallium (Ga) and zinc (Zn) nanowires. Enhancement of Ga and Zn superconducting transition temperature by 7 and 4 times. Big critical magnetic field enhancement for Ga and Zn nanowires@zeolite composite.